PENERAPAN MULTIMEDIA ANIMASI SEJARAH MENGGUNAKAN MODEL COOPERATIVE LEARNING â€œJIGSAWâ€ UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI MASA PERGERAKAN NASIONAL INDONESIA DI KELAS V SD N CIGENTUR KECAMATAN TANJUNGKERTA KABUPATEN SUMEDANG - Pazrin, Lustiana; Kurnia, Dadang; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2017)
Â This study aims to describe the application of multimedia animation history in improving the learning achievement of IPS students of grade V SD N Cigentur. This type of research is Action Research Class (Action Research). The research design used Kemmis and Mc Taggart model. The subjects of the study were the students of class V of 25 students consisting of 10 male students and 15 female students. Data collection techniques use observation, tests, field notes, and documentation. Data analysis technique is done descriptively, quantitative, and qualitative. The results showed that the use of multimedia can improve IPS learning achievement for students. The pre-action stage shows that the achievement of class V students in IPS subjects is low. The average grade value reached 43.68 while the learning mastery of 24%. In cycle I, students' learning mastery increased by 16% (initial condition 24% increased to 40%). In the second cycle, with the improvement and modification of multimedia learning, along with the management of group formation adapted to students 'cognitive abilities and reward, students' learning achievement increased by 48% (cycle I condition 40% increased to 88%). Learning achievement in cycle II has met the success indicator because 80% of students have reached score 70 .